Pengaruh Penggunaan Media Digital terhadap Prestasi Belajar Mahasiswa pada Mata Kuliah Pengelolaan Kelas Digital Program Studi Pendidikan Ekonomi - Risa Stephany; Riswan Jaenudin (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to prove the effect of the Use of Digital Media on Student Learning Achievement in the Digital Class Management Course in the Economics Education Study Program, Class of 2021, Sriwijaya University. This research is a quantitative study with a correlational research type. The population in this study were 75 students of Economics Education, Sriwijaya University Class of 2021. Sampling used the Total Sampling technique where the entire population was used as a sample of 75 students. Data collection techniques were questionnaires, interviews, and documentation. The validity test of the instrument used the Product Moment formula and reliability used Alpha Cronbach. The results of the study showed that the Digital Media data obtained were categorized as good with an average percentage of 82.2% and learning achievement showed an average of 86.44% which was categorized as very good. Data analysis using the t-test shows that t_(count) = 2.059 ≥ t_table = 1.994 then Ha is accepted and Ho is rejected, it can be concluded that there is an influence of the use of digital media on student learning achievement in the Digital Class Management course in the Economic Education Study Program, Class of 2021, Sriwijaya University. Based on this study, it is hoped that students will improve their knowledge of digital media even better so that student learning achievement will improve even better.